PENGARUH LIVE STREAMING SELLING, REVIEW PRODUCT, DAN DISCOUNT TERHADAP MINAT BELI KONSUMEN PADA E-COMMERCE SHOPEE - Ita Rahmawaty; Lailatus Sa’adah; Linda Musyafaah (Jurnal Riset Entrepreneurship, 2023)
The research conducted aims to determine the effect of live streaming selling, review product, and discount on consumer purchase intentions at e-commerce shopee. Quantitative research method used in this research. The population used in this study is infinite, therefore, taking the number of samples using the lameshow formula is 96 people rounded up to 100 people. And the analysis technique used is to carry out early detection and distribute questionnaires to shopee users who have met the criteria. The results of the study show that the live streaming sales variable has a significant influence because consumers experience direct interaction through social media. Product reviews also have a significant influence on purchase intentions, because consumers can determine the quality of the products offered. The discount variable also has a significant influence on purchase intention, because consumers think they will benefit from the discount given.